The rise of the mosque as a reflection of the religious metamorphosis of residential residents - Abdul Wahid Hasyim (IBDA` : Jurnal Kajian Islam dan Budaya, 2023)
A mosque is an efficient tool for inhabitants to engage in diverse religious activities, contributing to its prosperity, filling it with diverse religious activities, and fostering Islamic brotherhood ties between locals. This study explores the religious transformation of urban populations in the East Pamulang neighborhood of South Tangerang. The purpose of this study is to determine the tendency of solid religiosity of residents in four mosques in housing complexes, including Bukit Pamulang Indah complex (Al-Muhajirin mosque), Pamulang Indah complex (Darussalam mosque), Pamulang Estate complex (AtTaqwa mosque), and Vila Inti Persada complex (Inti Iman mosque). This research uses a qualitative method with a phenomenological perspective, showing an exciting interaction between the Mosque Prosperity Council and the community, which have diverse understandings of religion, ethnicity, culture, and regional origin. The excellent relationship between the Mosque Prosperity Council and the locals has increased the religiosity of Muslims in East Pamulang. For locals, a mosque is a place of worship and a space to create unity and improve family ties, encouraging East Pamulang residents to become dependent on the mosque, emotionally attached to it, and devoted to its growth